Late Presentation of Anorectal Malformations - A Dilemma in Modern World: Cross-sectional Analysis from a Tertiary Care Hospital, Pakistan - Sohail, Hamza; Nawaz, Tahir; Mirza, Mohammad Afzal; Ara, Jahan; Nawaz, Muhammad Ahsan; Arif, Anoshia; Ahmed, Moiz (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the presentation age of children with anorectal malformation and its relationship with complications.Study Design: Cross-sectional study.Place and Duration of Study: Children Hospital and Institute of Child Health, Faisalabad, from Jan to Dec 2019.Methodology: A total of 170 patients were included in the study. All the infants with a positive diagnosis of anorectal malformation from birth to 2 years of age were included in the study. Variables, including age at presentation, gender, diagnosis, length of stay and outcome in the form of discharge or mortality, were recorded.Results: A mean age of presentation was 3.4 ± 2.1 days. Out of the total 170 patients, 110 (64.71%) were males, and 60 (35.29%) were females. The age of children extended from birth to 2 years of age. It was observed that only 10 (5.88%) infants presented within 48 hours of birth, 110 (64.71%) neonates presented between 48 to 72 hours, while 50 (29.41%) presented after 72 hours. A mortality rate of 3.53% was observed in the late-presentation group, i.e., after 72 hours of birth. The length of hospitalization was longer in groups with late presentation.Conclusion: The present study reported that the majority of the infants with anorectal malformation were admitted to the hospital with a late presentation, i.e., after 72 hours of birth. Early and timely presentation of these infants can improve patient outcomes and reduce mortality among infants with anorectal malformations.